Payments for ecosystem services and social justice: Using recognition theories to assess the Bolivian Acuerdos Recíprocos por el Agua. Issue 92 (June 2018) - Bétrisey, Florence; Bastiaensen, Johan; Mager, Christophe
Highlights: Social justice in PES is not just about distribution, also about mutual recognition. PES may create new recognition channels and emancipate marginalized stakeholders. PES can reproduce conditions of misrecognition of the marginalized stakeholders. Stakeholders can make strategic use of recognition to improve their political power. Recognition theories show the ambiguity of the political implications of PES. Abstract: Payments for ecosystem services (PES) have been the subject of a great amount of literature among which questions of social justice are an important topic. However, we show that most of these studies tend to depoliticize the debate by considering mostly liberal and redistributive notions of justice. We argue that injecting the notion of recognition allows a better depiction of complex local power dynamics and situations of (in)justice. We, therefore, briefly review the social and political philosophical theories of recognition before using the notion of recognition as an analytical tool to assess a Bolivian PES ( Acuerdos Recíprocos por el Agua, ARA). We show how PES transform recognition relationships between upstream service providers and the formerly rather disinterested service consumers, including municipal authorities, by creating new narratives and channels of recognition. We also highlight the fragility of this process as well as the persisting misrecognition of the poorest of the poor (immigrants, small landowners) that is strengthened by this PES at the intra-community level. Finally, we highlight the potential instrumental use of recognition that could be made by PES promoters as well as counter-hegemonic use potentially made by marginalized actors.